Tính nhanh:
12+(23:3)x(43752754+48436345734)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) Tính:
1243 x 23 + 12 : 2 = 28589 + 6 =28595
23 x 786 : 3 x 12 = 18078 : 3 x 12 = 6026 x 12 = 72312
2) Tính nhanh:
12 x 4 + 23 x 2 x 2 = 12 x 4 + 23 x 4 = ( 12 + 23 ) x 4 = 35 x 4 = 140
9 x 19 + 3 x 19 - 2 x 19 = ( 9 + 3 - 2 ) x 19 = 10 x 19 = 190
\(\frac{12.23+23.88}{46.3+46.14}\)
\(=\frac{23.\left(12+88\right)}{46.\left(3+14\right)}\)
\(=\frac{23.100}{46.17}\)
\(=\frac{23.2.50}{23.2.17}\)
\(=\frac{50}{17}\)
\(\frac{12x23+23x88}{46x3+46x14}\)
=\(\frac{23x\left(12+88\right)}{46x\left(14+3\right)}\)
=\(\frac{23x100}{46x17}\)
= \(\frac{50}{17}\)
23 + 23 x 2 + 23 x 3 + 23 x 4
= 23 x (1 + 2 + 3 + 4)
= 23 x 10
= 230
246 x 2005 - 2005 x 148
= (246 - 148) x 2005
= 98 x 2005
= 196490
25 x 12 x 30 x 4
= (25 x 4) x 12 x 30
= 100 x 360
= 36000
= 23 x ( 45 + 78 + 12 )
= 23 x 135
= 3105
Ai tk mình thì mình tk lại
\(1,\frac{2}{3}+\frac{4}{9}+\frac{1}{5}+\frac{2}{15}+\frac{3}{2}-\frac{17}{18}\)
\(< =>\frac{4}{9}+\frac{3}{2}+\left(\frac{2}{3}+\frac{1}{5}+\frac{2}{15}\right)-\frac{17}{18}\)
\(< =>\frac{8}{18}+\frac{27}{18}+\left(\frac{10}{15}+\frac{3}{15}+\frac{2}{15}\right)-\frac{17}{18}\)
\(< =>\frac{35}{18}+1-\frac{17}{18}\)
\(< =>\frac{53}{18}-\frac{17}{18}\)
\(< =>2\)
\(2,\frac{13}{28}\cdot\frac{5}{12}-\frac{5}{28}\cdot\frac{1}{12}\)
\(< =>\left(\frac{13}{28}-\frac{5}{28}\right)\cdot\left(\frac{5}{12}-\frac{1}{12}\right)\)
\(< =>\frac{2}{7}\cdot\frac{1}{3}\)
\(< =>\frac{2}{21}\)
\(3,\frac{19}{4}\cdot\frac{15}{23}-\frac{15}{4}\cdot\frac{7}{23}+\frac{15}{4}\cdot\frac{11}{23}\)
\(< =>\frac{285}{92}-\frac{105}{92}+\frac{165}{92}\)
\(< =>\frac{15}{4}\)
a) 415 x 7 - 415 x 5 + 415 x 8
= 415 x (7 - 5 + 8)
= 415 x 10
= 4150
b) 23 x 87 + 12 x 23 + 23
= 23 x 87 + 12 x 23 + 23 x 1
= 23 x (87 + 12 + 1)
= 23 x 100
= 2300
3,5.23+7,12+10,5.9+14.6,5=3,5.23+3,5.24+3,5.27+3,5.26
=3,5.(23+24+27+26)=3,5.100=350
=\(\left(\dfrac{5}{17}+\dfrac{12}{17}\right)+\left(\dfrac{1}{22}-\dfrac{23}{22}\right)+\dfrac{2}{3}\)
=\(\dfrac{17}{17}-\dfrac{22}{22}+\dfrac{2}{3}\)
=\(1-1+\dfrac{2}{3}\)
=0+\(\dfrac{2}{3}\)
=\(\dfrac{2}{3}\)
1 2 + − 1 2 + − 2 3 + 2 3 + 3 4 + − 3 4 + − 4 5 + 4 5 + 5 6 + − 5 6 = 0
1 2 + − 1 2 + − 2 3 + 2 3 + 3 4 + − 3 4 + − 4 5 + 4 5 + 5 6 + − 5 6 = 0
Đây nha
mk lộn nha:12+(24:3)x(43752754+48436345734)